Essence and Phenomenon in Linguistic Content and Expression - Abrahamyan, Ashot (Armenian Folia Anglistika, 2009)
Essence – phenomenon and content – expression pairs comprise a net of interpenetrations in any language. The picture gets more complicated when the hierarchy of essence, phenomenon, content and expression is viewed on three levels of language generalization – in language in general, in a specific language and in an individual one. The phenomenon of the content of language in general and the essence of the content of an individual language, the phenomenon of expression of language in general and the essence of the expression of an individual language coincide in their order but not always in volume. There exists a relationship of possibility and reality between the essence of language in general and the phenomena of expression on the one hand and the essence of the individual language and the phenomena of expression on the other hand. It can be concluded that language in general and the individual language come closer not only in the phenomenon of the former and the essence of the latter, but, what is more remarkable, in the essence of the former and the phenomenon of the latter.